In vitro synergy between clofazimine and amikacin in treatment of nontuberculous mycobacterial disease - van Ingen, Jakko; Totten, Sarah E; Helstrom, Niels K; Heifets, Leonid B; Boeree, Martin J; Daley, Charles L (Antimicrobial agents and chemotherapy, 2012)
Disease caused by nontuberculous mycobacteria (NTM) is increasing in frequency. The outcome of treatment for NTM lung disease is poor, particularly lung disease caused by Mycobacterium simiae and M. abscessus. Exploring synergy between active available drugs is a sensible way forward given the lack of new active drugs. We tested for synergy between amikacin and clofazimine, using standardized methods, in 564 consecutive clinical isolates identified as 21 species of rapidly growing mycobacteria, 16 clinical M. avium complex isolates, and 10 M. simiae isolates. Clofazimine and amikacin are each active in vitro against NTM; 97% (n = 548) of the rapid growers revealed MICs of clofazimine of ≤1 μg/ml, and 93% (n = 524) proved susceptible to amikacin. The combination showed significant synergistic activity in 56 of 68 (82%) eligible M. abscessus isolates, 4 of 5 M. chelonae isolates, and 1 M. fortuitum and 1 M. cosmeticum isolate, with 4- to 8-fold decreases in MICs to both drugs. Significant synergy could also be demonstrated against all M. avium complex and M. simiae isolates, with fractional inhibitory concentrations of <0.5. Clofazimine and amikacin show significant synergistic activity against both rapidly and slowly growing nontuberculous mycobacteria. The safety and tolerability of adding clofazimine to amikacin-containing regimens should be tested in clinical trials, and the results of susceptibility tests for these two compounds and their combination merit clinical validation. Synergy between clofazimine and other antibiotics with intracellular targets should be explored.